2017
DOI: 10.4155/bio-2017-0009
|View full text |Cite
|
Sign up to set email alerts
|

Recommendations for Clinical Biomarker Specimen Preservation and Stability Assessments

Abstract: With the wide use of biomarkers to enable critical drug-development decisions, there is a growing concern from scientific community on the need for a 'standardized process' for ensuring biomarker specimen stability and hence, a strong desire to share best practices on preserving the integrity of biomarker specimens in clinical trials and the design of studies to evaluate analyte stability. By leveraging representative industry experience, we have attempted to provide an overview of critical aspects of biomarke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 16 publications
0
33
0
Order By: Relevance
“…Reasoning that an ideal miRNA biomarker should remain stable in plasma, we evaluated the freeze-thaw stability and short-term (bench-top) stability of samples, which were commonly encountered in clinical practice [38]. We randomly selected plasma samples from 6 healthy individuals, and their plasma samples were subjected to different conditions such as prolonged incubation at 4 °C (0 h, 1 h, 2 h, 6 h, 12 h, and 24 h, respectively) and repeated freeze-thaw cycles (0, 1, 2, and 4 times, respectively), as described in Supplemental Material (Section 6).…”
Section: Resultsmentioning
confidence: 99%
“…Reasoning that an ideal miRNA biomarker should remain stable in plasma, we evaluated the freeze-thaw stability and short-term (bench-top) stability of samples, which were commonly encountered in clinical practice [38]. We randomly selected plasma samples from 6 healthy individuals, and their plasma samples were subjected to different conditions such as prolonged incubation at 4 °C (0 h, 1 h, 2 h, 6 h, 12 h, and 24 h, respectively) and repeated freeze-thaw cycles (0, 1, 2, and 4 times, respectively), as described in Supplemental Material (Section 6).…”
Section: Resultsmentioning
confidence: 99%
“…While the discovery and development of biomarkers holds huge promise, it is clear that in order to draw meaningful conclusions, the analysis needs to be as close as possible to the time of collection of samples. This seemingly simple task is ridden with multiple challenges including preanalytic factors (e.g., collection, storage, shipping and handling), which can have a huge impact on the biomarker's stability, thereby affecting data reliability [48,49]. Since the impact on sample analysis can be quite substantial, it is important to evaluate sample collection and handling procedures in the assay development phase and subsequently provide the clinical sites with detailed instructions on controlling preanalytical variables [50] in a procedure manual (or lab manual), including specifics such as collection kits, collection tubes, exact pro-cessing methods with detailed steps, timing and temperature of each step, rate of freezing, aliquot size, etc.…”
Section: Matrixmentioning
confidence: 99%
“…-Existing literature outlining the FFP validation requirements [49,56] should be used, and layers of validation from CLSI documents added as appropriate to the COU.…”
Section: Biomarkersmentioning
confidence: 99%
“…It is, therefore, important that the storage temperature of samples is appropriate for the analyte tested [ 193 ]. Thus, biomarker studies should standardise and document the temperature and the duration of sample storage [ 194 ].…”
Section: Critical Evaluation Of Wet Biomarker Literature In Huntingtomentioning
confidence: 99%
“…As highlighted above, differences in sample preparation can influence absolute analyte levels. Therefore, to ensure that preanalytical variability is kept to a minimum in multi-centre studies, SOPs for collection, processing, storage and transport of samples should be created, formalised, and strictly adhered to [ 194, 197, 198 ]. The importance of standardising pre-analytical variables was clearly demonstrated in a study of BDNF in serum and plasma [ 189 ] where the authors found many issues concerning BDNF detection that make reliable measurement difficult.…”
Section: Critical Evaluation Of Wet Biomarker Literature In Huntingtomentioning
confidence: 99%